1996
DOI: 10.1111/1523-1747.ep12327199
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocytes in Human Wounds Express αvβ6 Integrin

Abstract: Cell adhesion receptors of the integrin family play a major role during re-epithelialization of human wounds. We have previously documented that the expression of alpha v family integrins is induced in keratinocytes of mucosal wounds [1]. In the present investigation, we extended these studies to determine whether alpha v beta 6 integrin is expressed during wound healing in humans. Mucosal and epidermal wound sections from 1- to 7-day-old wounds were used for immunolocalization of integrins and their putative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
121
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 25 publications
5
121
2
Order By: Relevance
“…α v β 6 is an exclusively epithelial integrin that is able to bind fibronectin and tenascin in the extracellular matrix (Sheppard et al, 1990;Prieto et al, 1993). Expression of α v β 6 integrin is induced during tumorigenesis and epithelial repair (Breuss et al, 1995;Clark et al, 1996;Haapasalmi et al, 1996). It has previously been shown that α v β 6 integrin is strongly expressed in SCCs of oral cavity (Breuss et al, 1995;Jones et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…α v β 6 is an exclusively epithelial integrin that is able to bind fibronectin and tenascin in the extracellular matrix (Sheppard et al, 1990;Prieto et al, 1993). Expression of α v β 6 integrin is induced during tumorigenesis and epithelial repair (Breuss et al, 1995;Clark et al, 1996;Haapasalmi et al, 1996). It has previously been shown that α v β 6 integrin is strongly expressed in SCCs of oral cavity (Breuss et al, 1995;Jones et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of α v β 6 integrin is, however, induced during wound healing and in squamous cell carcinoma (SCC) (Breuss et al, 1995;Haapasalmi et al, 1996). It is not known at which stage of transformation of oral epithelial cells to SCC the expression of α v β 6 integrin begins.…”
mentioning
confidence: 99%
“…A switch in integrin expression has often been described in epithelial cells. Indeed, while normal epithelial cells express collagen receptor α2β1 and laminin receptors α3β1 and α6β1 [79,80], hyperproliferating epithelial cells over-express αvβ5 and αvβ6 integrins [81,82] and the anoikis-resistant squamous carcinoma cells over-express αvβ6 with respect to αvβ5 [83,84]. This gradual change in integrin pattern expression allows cells to acquire enhanced invasiveness and anoikis resistance.…”
Section: Anoikis Resistance In Cancermentioning
confidence: 99%
“…11 Expression of a v b 5 integrin in the migrating keratinocytes may depend on the severity of the trauma, as it is expressed in deep human and porcine excisional skin wounds, but not in smaller incisional human skin or oral mucosal wounds. 101,102 For optimal motility on the wound composite matrix, keratinocytes seem to utilize several intermediate strength integrinmatrix interactions in cooperation. The strength of their cell adhesion may be regulated by focalized digestion of strong cell adhesion ligands, by assembly of matrices with reduced adhesiveness, by reduction of the strength of integrin affinity through cellular signaling, and by robust expression of low-affinity integrins.…”
Section: 99mentioning
confidence: 99%
“…6B). 102 It may mediate TGF-b1 activation and regulate ECM deposition in the granulation tissue (Fig. 8), 62 as its expression coincides with the peak expression and activity of this cytokine.…”
Section: 99mentioning
confidence: 99%